Another Consequence of the Warburg Effect? Metabolic Regulation of Na+/H+ Exchangers May Link Aerobic Glycolysis to Cell Growth - Birkeland, Eivind Salmorin; Koch, Lisa Maria; Dechant, Reinhard (Frontiers in Oncology, 2020)
To adjust cell growth and proliferation to changing environmental conditions or developmental requirements, cells have evolved a remarkable network of signaling cascades that integrates cues from cellular metabolism, growth factor availability and a large variety of stresses. In these networks, cellular information flow is mostly mediated by posttranslational modifications, most notably phosphorylation, or signaling molecules such as GTPases. Yet, a large body of evidence also implicates cytosolic pH (pHc) as a highly conserved cellular signal driving cell growth and proliferation, suggesting that pH-dependent protonation of specific proteins also regulates cellular signaling. In mammalian cells, cytosolic pH is regulated by growth factor derived signals and responds to metabolic cues in response to glucose stimulation. Importantly, high pHc has also been identified as a hall mark of cancer, but mechanisms of pH regulation in cancer are only poorly understood. Here, we discuss potential mechanisms of pH regulation with emphasis on metabolic signals regulating pHc by Na+/H+-exchangers. We hypothesize that elevated NHE activity and pHc in cancer are a direct consequence of the metabolic adaptations in tumor cells including enhanced aerobic glycolysis, generally referred to as the Warburg effect. This hypothesis not only provides an explanation for the growth advantage conferred by a switch to aerobic glycolysis beyond providing precursors for accumulation of biomass, but also suggests that treatments targeting pH regulation as a potential anti-cancer therapy may effectively target the result of altered tumor cell metabolism.